Mathematical Critical Thinking in HOTS Problems With a Malay Cultural Context - Nur Izzati; Anggia Rahmawati; Azizah Demokratia ‘Adilah; Laila Rahmadani Ali Nasution; Siska Amanda (Riemann: Research of Mathematics and Mathematics Education, 2026)
This study investigates students’ mathematical critical thinking skills in solving Higher Order Thinking Skills (HOTS) problems contextualised within Malay culture, focusing on two-variable linear equation systems. Although numerous studies have examined critical thinking in mathematics, limited research integrates local cultural contexts into HOTS problem design. This qualitative descriptive study involved three ninth-grade students selected purposively from different critical thinking categories (high, medium, and low). Data were collected through written tests and semi-structured interviews based on Facione’s six critical thinking indicators: interpretation, analysis, evaluation, inference, explanation, and self-regulation. The findings reveal distinct characteristics across ability levels. Students in the high category were able to interpret contextual information accurately, construct appropriate mathematical models, and explain their reasoning logically before concluding, although minor computational inaccuracies occasionally occurred. Students in the medium category showed adequate ability in identifying relevant information and modelling the problem but experienced difficulties in organising information systematically and formulating precise conclusions. Meanwhile, students in the low category demonstrated limited ability in translating contextual problems into mathematical representations and expressing coherent reasoning in written form. The integration of Malay cultural contexts supported meaningful engagement, yet critical thinking development remained dependent on students’ cognitive readiness. These findings highlight the importance of contextual HOTS problem design combined with structured metacognitive scaffolding in mathematics instruction.